Influence Of Minimum Capital And Investment Learning Education On Investment Interest In The Sharia Capital Market (A Study On Investors Of The Sharia Investment Gallery) - Renda Marisa; Eka Sri wahyuni; Yunida Een Friyanti (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to find out and analyze the influence of minimum capital and investment learning education on investment interest in the sharia capital market, with a study on sharia investment gallery investors. Methodology: The type of research used was a quantitative approach and consisted of primary data through the distribution of Google Form questionnaires to 71 respondents who were investors in the sharia investment gallery of UIN Fatmawati Sukarno Bengkulu. The data obtained was then analyzed using multiple regression techniques with the help of the SPSS version 15 program. Results: Based on the results of the research and discussion, it was found that minimum capital has a significant influence on investment interest, with a significance value of 0.002 which is smaller than 0.05. In addition, investment learning education did not have a significant influence on investment interest, with a significance value of 0.054 which was greater than 0.05. Findings: The findings confirm that minimum capital serves as a primary determinant of investment interest, whereas investment learning education appears to play a less critical role in shaping investor decisions in this particular context. Novelty & Originality: The novelty of this study lies in its focus on sharia capital market investors within a university-based sharia investment gallery in Bengkulu, an under-researched setting in Islamic finance literature. Its originality emerges from the simultaneous testing of both financial and educational factors influencing investment interest among retail investors in the sharia capital market. Conclusions: Thus, it can be concluded that minimum capital has a significant impact on investors' interest in investing in the sharia capital market, while investment learning education does not have a significant influence. Type of Paper: This paper is an empirical research paper.